2012
DOI: 10.2527/jas.2011-4052
|View full text |Cite
|
Sign up to set email alerts
|

Increasing energy and lysine in diets for growing-finishing pigs in hot environmental conditions: Consequences on performance, digestibility, slurry composition, and gas emission1

Abstract: The influence of dietary nutrient concentration on growth performance, manure composition, and gas emission was studied in pigs in hot environmental conditions. A total of 64 intact males and 64 females [(Landrace × Large White) × Pietrain] weighing 63.1 ± 9.7 kg were divided into 2 dietary treatments: high (HD: 14.39 MJ of DE/kg and 1.11% Lys) and low (LD: 13.97 MJ of DE/kg and 1.01% Lys) in energy and Lys contents. Pigs were allocated to 32 split-sex pens with 4 pigs/pen and 16 pens/treatment. Average produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The protein and fat content in faeces, however, was not different between treatments. Methane emission from faeces is directly related with slurry composition (IPCC, 2006;Jarret et al, 2011a,b;Cerisuelo et al, 2012). Methane production is the result of the degradation of organic compounds by methanogenic archaea.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The protein and fat content in faeces, however, was not different between treatments. Methane emission from faeces is directly related with slurry composition (IPCC, 2006;Jarret et al, 2011a,b;Cerisuelo et al, 2012). Methane production is the result of the degradation of organic compounds by methanogenic archaea.…”
Section: Discussionmentioning
confidence: 98%
“…Diet composition has been identified as one of the most important factors influencing methane and other gas emission from slurry (Aarnink and Verstegen, 2007;Jarret et al, 2011a,b;Cerisuelo et al, 2012). In this regard, nutritional strategies have been identified as the first step for reducing the environmental impact of animal slurries by the document on Best Available Techniques for intensive rearing of poultry and pigs published by the Integrated Pollution Prevention and Control organism (IPPC, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…However, in the present study, replacing SBM with 4% RSM or CM had no negative effect on blood characteristics in finishing pigs. Faecal noxious gas emission and meat quality were regarded as one of the most important criteria of feed formulation in pig diets (Apple et al 2002;Aarnink and Verstegen 2007;Cerisuelo et al 2012). In the present study, pigs fed with RSM had no negative effects on faecal noxious gas emission (ammonia, total mercaptans, and hydrogen sulphide) and on meat quality such as meat colour, sensory evaluation, drip loss, pH, LMA, and WHC as compared with those fed with SBM.…”
Section: Itemsmentioning
confidence: 57%
“…In this respect, Cámara et al (2014) reported a linear increase in ADG of the pigs as the energy content of the diet increased. In contrast, Cerisuelo et al (2012) reported similar ADFI and ADG with an increase in the DE content of the diet from 14.0 to 14.4 MJ DE/kg.…”
Section: Introductionmentioning
confidence: 83%
“…However, an increase in the NE content of the diet often results in greater energy intake and fatter carcasses (Cámara et al, 2014). On the other hand, high CP diets are often used to increase the safety margins of indispensable AA resulting in increases in N excretion and the emission of gas to the environment (Møller et al, 2004;Dinuccio et al, 2008) which reduces the interest of this practice (Cerisuelo et al, 2012). The use of crystalline AA allows to reduce the CP content of the diets while maintaining growth performance (Kerr et al, 2003).…”
Section: Introductionmentioning
confidence: 99%